PENGARUH LITERASI KEUANGAN DAN SISTEM PEMBAYARAN DIGITAL TERHADAP KINERJA UMKM DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Busrin Raihana Mas’ud; Isma B; Fadlina Fadlina (Universitas Ichsan Sidenreng Rappang, 2025)
The research is motivated by the phenomenon that occurs because it sees that MSMEs in sidenreng rappang regency, especially in maritengngae district, are not a few MSME actors going bankrupt due to tight competition, lack of knowledge about financial management or known as financial lyteracy which results ini MSME actors being unable to manage their businesses well and in the current digitalization era there are still many MSME actors who have not used a digital payment system that makes it easier to make transactions without cash and do not need to provide change if the consumer’s money is more than the total payment. The purpose of this study was to determine the effect of financial literacy and digital payment systems on the performance of MSMEs. The type of research used in this study is quantitative. The population in this study were all MSME actors in Maritengngae District, Sidenreng Rappang Regency. The sample in this study amounted to 61 respondents. Sampling used the lemeshow formula. The data collection technique used a questionnaire with a Likert scale, each of which had been tested and had met the validity and reliability requirements. The analysis method used in this study was multiple linear regression. The results of multiple linear regression analysis show that financial literacy and digital payment variables simultaneously have a positive effect on the performance of MSMEs in Maritengngae District, Sidenreng Rappang Regency. This can be proven from the F-count value (18.276> 3.16) with a significance value (sig) of 0.00 <0.05 (a = 5%). Based on the results of the t-test, the financial literacy variable has a positive value with a t-count value of 4.683> a t-table value of 2.002 and a significance value of 0.00 <0.05. This shows that the financial literacy variable has a positive and significant effect on the MSME performance variable and based on the results of the t-test, the digital payment variable has a positive value with a t-count value of 2.342> a t-table value of 2.002 and a significance value of 0.023 <0.05. This shows that the digital payment variable has a positive and significant effect on the performance variable of MSMEs in Maritengngae District, Sidenreng Rappang Regency.